Trade Protection and the Location of Production - Susanna Thede (Lund University, School of Economics and Management, Department of Economics, 2002)
This study examines the economic role of trade protection in a new economic geography model where countries have no inherent differences in endowments, preferences or technologies. This is done in two ways. First, the effects of agricultural and manufacturing protection on the set of equilibria are obtained. Second, the endogenous trade policy positions resulting from a game between national welfare-maximising governments are identified. The model used is a Krugman & Venables (1995) model modified to incorporating agricultural trade costs. Therefore, an additional contribution is the examination of the effect of agricultural trade costs on the equilibrium structure of the model.
Keywords: F12; F13; 330; new economic geography; endogenous trade policies; agricultural trade costs